Specificity and Combinatorial Effects of Bacillus Thuringiensis Cry Toxins in the Context of GMO Environmental Risk Assessment - Hilbeck, Angelika; Otto, Mathias (Frontiers in Environmental Science, 2015)
Stacked GM crops expressing up to six Cry toxins from Bacillus thuringiensis are today replacing the formerly grown single- transgene GM crop varieties. Stacking of multiple Cry toxins not only increase the environmental load of toxins but also raise the question on how possible interactions of the toxins can be assessed for risk assessment, which is mandatory for GM crops. However, no operational guidelines for a testing strategy or testing procedures exist. From the developers point of view, little data testing for combinatorial effects of Cry toxins is necessary as the range of affected organisms is focused on pest species and no evidence is claimed to exists pointing to combinatorial effects on nontarget organisms. We have examined this rationale critically using information reported in the scientific literature. To do so we address the hypothesis of narrow specificity of Cry toxins subdivided into three underlying different conceptual conditions i) 'efficacy' in target pests as indicator for 'narrow specificity', ii) lack of reported adverse effects of Cry toxins on nontarget organisms, and iii) proposed modes of action of Cry toxins (or the lack thereof) as mechanisms underlying the reported activity/efficacy/specificity of Cry toxins. Complementary to this information we evaluate reports about outcomes of combinatorial effect testing of Cry toxins in the scientific literature and relate those findings to the practice of the environmental risk assessment of Bt-corps in general and of stacked Bt-events in particular.